2018
DOI: 10.1016/j.isci.2018.11.020
|View full text |Cite
|
Sign up to set email alerts
|

A Bifunctional Fluorophosphate Electrolyte for Safer Sodium-Ion Batteries

Abstract: SummaryMost of the currently developed sodium-ion batteries (SIBs) have potential safety hazards due to the use of highly volatile and flammable alkyl carbonate electrolytes. To overcome this challenge, we report an electrochemically compatible and nonflammable electrolyte, tris(2,2,2-trifluoroethyl) phosphate (TFEP) with low-concentration sodium bis(fluorosulfonyl)imide (0.9 M), which is designed not only to match perfectly with the hard carbon (HC) anode but also to enhance the thermal stability of SIBs. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 54 publications
2
49
0
Order By: Relevance
“…Actually, fluoroalkyl phosphates have been proved to be highly effective for SEI formation on carbonaceous electrodes. Moreover, partial F substitution is also helpful for further reducing the flammability of electrolytes because of a synergistic flame retardant effect between F and P . In 2018, Jiang et al reported an electrolyte of 0.9 m NaFSI in tris(2,2,2‐trifluoroethyl) phosphate (TFEP) for Na 3 V 2 (PO 4 ) 3 ||hard‐carbon full cell.…”
Section: Nonaqueous Electrolytes For Sibsmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, fluoroalkyl phosphates have been proved to be highly effective for SEI formation on carbonaceous electrodes. Moreover, partial F substitution is also helpful for further reducing the flammability of electrolytes because of a synergistic flame retardant effect between F and P . In 2018, Jiang et al reported an electrolyte of 0.9 m NaFSI in tris(2,2,2‐trifluoroethyl) phosphate (TFEP) for Na 3 V 2 (PO 4 ) 3 ||hard‐carbon full cell.…”
Section: Nonaqueous Electrolytes For Sibsmentioning
confidence: 99%
“…The electrolyte of 0.9 m NaFSI/TFEP is nonflammable and matched well with hard‐carbon electrode. Because of enhanced electrochemical and structural stabilities of hard‐carbon electrodes, the Na 3 V 2 (PO 4 ) 3 ||hard‐carbon full cell with 0.9 m NaFSI/TFEP electrolyte showed a high capacity retention of 89.2% after 300 cycles and a dramatically reduced exothermic heat at elevated temperature . Generally, organic phosphate‐based electrolytes are nonflammable and show great potential for practical applications.…”
Section: Nonaqueous Electrolytes For Sibsmentioning
confidence: 99%
“…Therefore, it would be more economical and convenient to enhance the safety by modifying the components of the current mature electrolyte system, instead of changing its skeleton composition. The inclusion of conventional flame‐retardant additives, for instance, dimethyl methylphosphonate, tris(2,2,2‐trifluoroethyl) phosphate, and trimethyl phosphate, is a promising method, and meanwhile, a small dose of ILs might also be proposed as electrolyte additive to address the cycling instability and safety issues of SIBs . At present, the investigation on these functional solvents should be strengthened for safer organic electrolytes.…”
Section: Summary and Perspectivementioning
confidence: 99%
“…C, Ignition test of EC/DEC and TFEP solvent and DSC profiles of NaV 2 (PO 4 ) 3 and Na x C in carbonate and TFEP electrolytes. Reproduced with permission 55 . Copyright 2018, Elsevier Ltd. D, Overview of the physicochemical properties of the electrolytes with different concentrations, the variations of interactions between molecules/ions and interfacial components, and the concentration dependence of ionic conductivity and viscosity at 25°C and 0°C for NaPF 6 in EC/PC electrolyte.…”
Section: Electrolytes For All‐climate Sibsmentioning
confidence: 99%